Impact of land uses on water quality in Malaysia: a review - Moriken, Camara; Jamil, Nor Rohaizah; Abdullah, Ahamd Fikri (SpringerOpen, 2019)
Land use changes in urbanization, industrialization, and agricultural processes will continue to have negative impacts on water quality at all scales. The impact of land use changes on water quality is generally studied by analyzing the relationships between land use and water quality indicators. Therefore, the purpose of this research was to review and analyze the main relationships between land use and water quality, as well as to visualize the major sources and processes of water quality pollution in Malaysia. To achieve our goal, we evaluated the significance of both land use and water quality attributes used in the past studies and correlated them to understand their relationship from another angle of view. The results revealed that 87% of the reviewed studies indicated urban land use as a major source of water pollution, while 82% indicated agricultural land use, 77% indicated forest land use, and 44% indicated other land uses. However, the results of correlation analysis showed that agricultural and forest-related activities more affected water quality through their significant positive correlation with physical and chemical indicators of water quality, while urban development activities had a greater impact on water quality through altering hydrological processes such as runoff and erosion. These findings would provide decision-makers with useful information for managing water pollution processes rather than sources only.